Kinetics of Oxidation of Some Cycloalkanones by Alkaline Hexacyanoferrate(III) - K. Sati, Mukul; Singh, Pratibha; Tewary, Geeta; Mehta, S.P.S. (Asian Journal of Chemistry, 2010)
The oxidation of cyclopentanone, cyclohexanone, cycloheptanone and cyclooctanone. by alkaline hexacyanoferrate(III) follows the same kinetics in the absence of any catalyst. The study indicated that: (i) even the uncatalysed oxidations of cycloalkanones by aqueous alkaline hexacyanoferrate(III) are fast reactions. (ii) the order of the reactivity is cyclohexanone ≥ cyclopentanone ≥ cyclooctanone ≥ cycloheptanone.